2020
DOI: 10.1016/j.eclinm.2020.100268
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a nine-month regimen for rifampicin-resistant tuberculosis up to 24 months after treatment completion in nine African countries

Abstract: Background: Treatment outcomes of the shorter regimen for rifampicin-resistant tuberculosis are not completely established. We report on these outcomes two years after treatment completion among patients enrolled in an observational cohort study in nine African countries. Methods: 1,006 patients treated with the nine-month regimen were followed every six months with sputum cultures up to 24 months after treatment completion. The risk of any unfavourable outcome, of failure and relapse, and of death during and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Gastro-intestinal events were more common in other studies (54.6–57.1%) compared to Burundi, where light meals prior to drug administration during the intensive phase may have prevented disturbances [ 6 , 11 , 12 ]. The most debilitating AE were hearing loss and tinnitus, occurring in one in ten patients, less frequent than in other studies on STR (25.3–44.3% [ 3 , 4 ]) and 36% in other cohorts with >20% HIV-positive patients [ 12 ]. Regular audiograms were taken at the same frequency compared to the nine-country study (at initiation and month four), but less frequent than in Niger (also at month two) [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Gastro-intestinal events were more common in other studies (54.6–57.1%) compared to Burundi, where light meals prior to drug administration during the intensive phase may have prevented disturbances [ 6 , 11 , 12 ]. The most debilitating AE were hearing loss and tinnitus, occurring in one in ten patients, less frequent than in other studies on STR (25.3–44.3% [ 3 , 4 ]) and 36% in other cohorts with >20% HIV-positive patients [ 12 ]. Regular audiograms were taken at the same frequency compared to the nine-country study (at initiation and month four), but less frequent than in Niger (also at month two) [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 61%
“…We had a very high coverage of post-treatment follow-up; 94.7% had at least one follow-up visit, and 83.8% were followed a year or more after treatment ended. This is much higher compared to the African nine-country study, where only 57.2% of patients were followed until a year after completion [ 3 ]. Any missing data, inconsistencies or doubts were verified by checking the original patient files.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…She was started on the STR 1 day after the diagnosis of rifampicin-resistant TB, as per routine practice in Rwanda. As per national guidelines adapted from a previous survey protocol, 6 based on the patient’s weight, the initiated STR comprised moxifloxacin (200 mg), kanamycin (500 mg), protionamide (500 mg), ethambutol (600 mg), clofazimine (100 mg), isoniazid (300 mg), and pyrazinamide (800 mg).…”
Section: Case Reportmentioning
confidence: 99%
“…A study on the implementation of the shorter MDR-TB treatment regimen in nine African countries found that isoniazid susceptibility was associated with a significantly lower risk of bacteriological failure. Since testing for isoniazid resistance is still difficult and often not done, this is another reason to use isoniazid indiscriminately for all rifampicin-resistant TB (RR-TB; Schwœbel et al, 2020 , Trébucq et al, 2018 ). Resistance also to isoniazid (MDR-TB) is highly prevalent in RR-TB isolates ( WHO, 2019a ), but the frequency of the highest level of resistance, conferred by double mutations in katG and inhA ( Ghodousi et al, 2019 , Lempens et al, 2018 ), is low (<5% in most settings) ( Seifert et al, 2015 ), and the association between different levels of resistance to the drug and treatment outcome remains unclear.…”
Section: Introductionmentioning
confidence: 99%